Influence of Protein Source on Growth Performance in Nursery Pigs - Ethan B. Stas; Mike D. Tokach; Robert D. Goodband; Jason C. Woodworth; Joel M. DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 330 pigs (241 × 600, DNA; initially 10.7 lb) were used to determine the influence of dietary protein source on growth performance in nursery pigs. At weaning, pigs were randomly allotted to 1 of 6 dietary treatments with 4 or 5 pigs per pen and 12 replications per treatment. Dietary treatments were arranged in a one-way treatment structure with diets containing different protein sources; enzymatically treated soybean meal (HP 300; Hamlet Protein, Findlay, OH), spray-dried bovine plasma (APC Corp, Ankeny, IA), fermented soybean meal (ME-PRO; Prairie Aquatech, Brookings, SD) with or without fish solubles (TASA, Lima, Peru), fish meal (TASA Prime meal; TASA, Lima, Peru), and custom-made fish meal (TASA Swine; TASA, Lima, Peru). Because of a delay in arrival of the fish meal source, all pigs were placed on a common phase 1 diet for 3 d after weaning. On d 3, all feeders were weighed, dumped, and refilled with experimental diets. Pigs were fed experimental phase 1 diets for 9 d (d 3 to 12) followed by phase 2 diets for 15 d. Following phase 2, all pigs were fed a common diet for an additional 15 d. In all weigh periods and overall, there were no significant differences between treatments for BW, ADG, ADFI, and F/G. For economic analysis (d 0 to 40), pigs fed spray-dried bovine plasma had the greatest (P≤ 0.001) feed cost and feed cost per lb of gain compared to all other treatments. There were no differences in revenue or IOFC between treatments. In summary, utilizing alternative protein sources in phase 1 and 2 nursery pigs’ diets had no effect on growth performance. However, there was a 5 to 7% improvement in ADG for pigs fed spray-dried bovine plasma and custom-made fish meal.
Keywords: anchovy fish meal; fish solubles; nursery pigs